UV-ageing effects on polystyrene microplastics surface polarity and transport in soils - Leila Shafea; Marc-O. Goebel; Susanne K. Woche; Stephan Peth (Environmental Challenges)
Microplastics (MP) in soils are considered an emerging environmental pollutant of global concern. The transport processes of MP in soils are poorly understood, which indicates a major knowledge gap regarding the environmental impact and behaviour of MP. Mobility and surface charge can be affected by ageing, mainly via UV irradiation. In the present study, 1 µm polystyrene microspheres (PS-MP) were aged with UV irradiation using an irradiance of 2.05 W m−2 (ultraviolet A, UVA; 365 nm) and 5.58 W m−2 (ultraviolet C, UVC; 254 nm) and different exposure times between 24 und 1176 hours to generate a gradient in MP ageing. The UV-ageing effects on PS-MP were characterised in terms of changes in particle size, zeta potential, and surface functional groups as determined by attenuated total reflectance Fourier-transform infrared spectroscopy (ATR-FTIR). Non-irradiated PS-MP microspheres were used as a control. Column tests were performed by percolating PS-MP microspheres suspended in CaCl2 solution (ionic strength 7.5 mM) through a quartz sand matrix (0.3 mm particle diameter). PS-MP sizes steadily decreased with increasing ageing time from 24 h to 1176 h for both UVA and UVC treatment. ATR-FTIR results revealed that UV irradiation induced a transformation of PS-MP surfaces with especially the appearance of a carbonyl (C=O) peak due to C-H bond breaking during the oxidation process. The increasing presence of oxygen-containing functional groups in UV-treated PS-MP led to an increasing negative surface charge and zeta potential and enhanced PS-MP transport through the quartz sand column. With increasing irradiation time, the aged PS-MP showed continuously increasing transport rates compared to the transport rates of non-aged PS-MP, ranging from 46 to 85% and 48 to 91% for UVA- and UVC-treated samples, respectively. The fastest breakthrough was observed for highest negative zeta potential and amount of O-containing functional groups as compared to control PS-MP, which enhanced electrostatic repulsion between aged PS-MP and quartz sand particles as was demonstrated from calculation of the interaction free energy. Our findings imply that UV irradiation changes the PS-MP surface physicochemical characteristics and transport potential by increasing the mobility of PS-MP and hence the risk for contamination of deeper soil layers and water bodies.